Rancher Perceptions of the Coyote in Florida - Raoul K. Boughton; Bethany Wright; Martin B . Main (EDIS)
Throughout the continental United States and large portions of Canada and Central America, changes people make to the landscape such as the clearing of forested land and the extermination of larger predators like gray and red wolves have made the environment perfect for the adaptive coyote. Coyotes have rapidly taken advantage of these environmental shifts and expanded into new areas, now including all 67 counties in Florida and even Key Largo. Each year more people in Florida catch a glimpse of a coyote crossing a road or running across open fields, or notice coyote scat along a hiking trail–and farmers and ranchers are seeing signs of coyotes on their farms.